Artificially induced pneumothorax with a Veress needle for cryoablation of renal cell carcinoma. Issue 3 (1st March 2022) - Maeda, Hitomi; Kajiwara, Kenji; Yoshimatsu, Rika; Yamanishi, Tomoaki; Minamiguchi, Hiroki; Karashima, Takashi; Inoue, Keiji; Awai, Kazuo; Yamagami, Takuji
Abstract: Thermal ablative techniques are used increasingly to treat renal cell carcinoma (RCC). Percutaneous cryoablation of tumors at the upper pole of the kidney may result in pulmonary damage due to the intervening lung parenchyma. We treated two patients with RCC in the upper pole of the kidney by inducing pneumothorax with a pneumoperitoneum needle before proceeding to percutaneous cryoablation. The procedures, performed under computed tomography (CT) fluoroscopy guidance, resulted in complete tumor necrosis. There was no pulmonary damage.